2018
DOI: 10.1177/2473011418804487
|View full text |Cite
|
Sign up to set email alerts
|

Total Ankle Replacement Conversion to Tibiotalocalcaneal Arthrodesis With Bulk Femoral Head Allograft and Pseudoelastic Intramedullary Nail Providing Sustained Joint Compression

Abstract: Tibiotalocalcaneal (TTC) arthrodesis is commonly performed to salvage a failed total ankle replacement. These salvage procedures are complicated by significant bone loss from the ankle replacement and are associated with low patient satisfaction. Here, we describe 2 cases of patients who presented with a failed total ankle replacement and underwent arthrodesis using a bulk femoral head allograft and a novel pseudoelastic intramedullary nail. The intramedullary nail contains an internal pseudoelastic element th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…4,7,10,[13][14][15]17,19,20,[22][23][24][25][26][28][29][30]32 More recent studies have indicated that the rates for bulk FHA fusion are higher than previously reported. 3,5,6,8,[10][11][12]14,19,24,29,32 Myerson et al 21 found that allografts were suitable for use in the foot and ankle and avoided the potential complications associated with harvesting autografts, reduced operative time and cost, and effectively filled volumes too large for traditional autografts. However, these bulk allograft materials introduce new challenges with achieving fusion given their relatively poor healing capacity and propensity to resorb (and potentially collapse) over time.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,10,[13][14][15]17,19,20,[22][23][24][25][26][28][29][30]32 More recent studies have indicated that the rates for bulk FHA fusion are higher than previously reported. 3,5,6,8,[10][11][12]14,19,24,29,32 Myerson et al 21 found that allografts were suitable for use in the foot and ankle and avoided the potential complications associated with harvesting autografts, reduced operative time and cost, and effectively filled volumes too large for traditional autografts. However, these bulk allograft materials introduce new challenges with achieving fusion given their relatively poor healing capacity and propensity to resorb (and potentially collapse) over time.…”
Section: Discussionmentioning
confidence: 99%
“…CT data was used to create CAD models of the tibia, talus, and calcaneus, which were combined with device CAD files of the TTCA hardware. to TTCA with the SCN and bulk femoral head allografts [79]. Both patients experienced CT-assessed union of all joints.…”
Section: Potential Drawbacks Include Patient Noncompliance and Limitedmentioning
confidence: 99%
“…This element-provided compression is retained during potential bone resorption at the joint surfaces or joint settling which may occur post-operatively during the arthrodesis process. If this occurs, the distal screws will shift proximally within slots, along with the connected calcaneus [45,[77][78][79].…”
Section: Potential Drawbacks Include Patient Noncompliance and Limitedmentioning
confidence: 99%
“…Reviews of published clinical literature have documented TTC arthrodesis union rates as high as 94.6%; however, the occurrence of non-union can be seen in up to 50% of procedures involving complex cases of ankle disease (e.g., revision surgeries, diabetes, Charcot neuroarthropathy, tobacco usage, bulk bone defect, etc.) [3][4][5][6][7]. For these challenging cases, newer devices that enable dynamization of the arthrodesis construct (intermittent compressive loading transferred to the bone via elongated screw slots or other sliding mechanisms) may provide for better fusion outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Because sustained compression is advantageous for achieving proper fusion, localized bone resorption at the fusion site is of concern. Studies evaluating the clinical performance of pseudoelastic intramedullary (IM) nails have reported average radiographically measured values of resorption-induced shortening ranging from 3.1 mm to 5.6 mm [4,6,14,15]. This degree of shortening would be expected to result in a decrease in compression across the TTC complex; however, the extent of the loss of compression has not been quantified.…”
Section: Introductionmentioning
confidence: 99%